Persepsi Siswa pada Layanan Bimbingan dan Konseling di SMK Negeri 1 Aceh Tenggara - Sopia Barira; Ramadhan Lubis; Nurhayani Nurhayani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The research conducted was entitled "Students' perceptions of counseling guidance at SMK Negeri 1 Southeast Aceh", which was based on the fact that only a small percentage of students had the initiative to provide counseling to guidance and counseling teachers at SMK Negeri 1 Southeast Aceh. This research method uses a descriptive qualitative research approach aimed at describing, writing and explaining in detail the problems to be researched and studying an individual or a group. The subject selection technique is based on the criteria set by the researcher. Data collection techniques using observation, interviews and field notes. Data analysis uses data reduction, data presentation and conclusion drawing to test the validity of the data using primary data and secondary data. The research results revealed that (1) that students' perceptions of good counseling guidance were characterized by a good response in following the lessons delivered by counseling guidance through orientation services. Apart from that, there are still students who show bad attitudes towards the guidance and counseling teacher. The guidance and counseling teacher's efforts are also complemented by a service delivery plan (RPI) and carrying out routine evaluations of students both individually and in study groups. (2) The BK teacher takes steps to prevent the decline in students' trust in counseling guidance before students' trust in counseling guidance. The guidance and counseling teacher coordinates with the school principal and then the school will take action by bringing in lecturers from outside the school to rebuild students' declining confidence. (3) The time that Bk teachers have to enter Rombel is also limited so that BK teachers experience difficulties in carrying out orientation. Guidance and counseling teachers can only rely on the time provided by the school for students and what class they go to if a class teacher is absent because they are absent. Apart from that, the guidance and counseling teachers in schools are also lacking, making it difficult for guidance and counseling teachers to handle large numbers of students.